A corpus-based approach to mind style. - McIntyre, Dan; Archer, Dawn (Journal of Literary Semantics)
Fowler's (Linguistics and the novel, Methuen, 1977) original definition of mind style emphasised consistency as a defining feature of the phenomenon, something that is (i) difficult to measure, and (ii) often missed in qualitative analyses. In this paper we investigate how a computational semantic analysis might be used to address this difficulty, with particular reference to McIntyre's (Journal of Literary Semantics 34: 21–40, 2005) analysis of the deviant mind style of the character of Miss Shepherd in Alan Bennett's play The Lady in the Van. To do this we analyse the speech of all the characters in The Lady in the Van using Wmatrix (Rayson, Matrix: A statistical method and software tool for linguistic analysis through corpus comparison, Lancaster University PhD thesis, 2003, Wmatrix: A web-based corpus processing environment, Lancaster University, 2008), to see whether it provides quantitative support for the interpretative conclusions reached by McIntyre. Wmatrix utilises the UCREL Semantic Annotation System (USAS) which has been designed to undertake the automatic semantic analysis of English. The initial tag-set of the USAS system was loosely based on McArthur's Longman Lexicon of Contemporary English (McArthur, Longman, 1981), but has since been considerably revised in the light of practical tagging problems met in the course of previous research, and now contains 232 category labels (such as medicine and medical treatment, movement, obligation and necessity, etc.). We use Wmatrix's facility for identifying key semantic domains in pursuit of our two main aims: (i) to determine whether Miss Shepherd's odd mind style is consistent, as Fowler's definition suggests it should be; and (ii) to determine the usefulness of computational semantic analysis for investigating mind style.